Antidepressant-Like Effects of Ceftriaxone in Chronic Unpredictable Mild Stress Model in Rats: The Importance of Reuptake Time of Glutamate - ARICIOĞLU, FEYZA (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: We aimed to indicate the relationship between depression and glutamate, and to reveal the effect of escitalopram, an antidepressant, which is widely used in depression treatment and reuptake parameters of glutamate, and to treat depression with ceftriaxone, one of the beta lactam antibiotics which increased the number and activity of glutamate transporters. Methods: In CUMS, rats subjected to series of different mild stressors in an unpredictable manner for 40 days. On the day 20 rats were divided in to groups such as CUMS, CUMS+Escitalopram and CUMS+Ceftriaxone. 4 weeks. Treatments were started at 2nd week of CUMS and continued for 21 days. Anhedonia and antidepressant effect were assessed by sucrose preference (SP), locomotor activity (LA), elevated plus maze (EPM) and forced swim test (FST) at the end of the experiment respectively. At the end of the experiment, behavioral tests were made, and glutamate reuptake time in CA3 (cornuammonis 3) brain region which are related with depression were measured by means of in vivo voltammetry technique. Results: Ceftriaxone treatment had an antidepressant-like effect. Escitalopram and ceftriaxone increased SP and locomotor activity, reduced immobility FST, forced swim and time spent in closed arms in EPM compared to CUMS group. In this in-vivo voltametric study, it was also observed that there was a significant decrease in glutamate reuptake time in depression. Conclusion: Escitalopram and ceftriaxone demonstrated antidepressant-like effects by reversing behavioral changes in CUMS model. Escitalopram treatment in CA3 region corrected the decrease in glutamate reuptake time which is consistent with the hypothesis that enhanced uptake of glutamate might have antidepressant-like effects.
Keywords: Beta lactam antibiotics; ceftriaxone; depression; voltammetry; glutamate; DEPRESSION; TRANSPORTERS; HIPPOCAMPUS; EXPRESSION; MOUSE